Water Privatization and Inequality: Gini Coefficient for Water Resources in Chile - Correa Parra, Juan Pablo.; Vergara Perucich, José Francisco.; Aguirre Núñez, Carlos. (MDPI, 2020)
This document makes a comprehensive analysis of the inequality of the water market in Chile, measured by the Gini coefficient method. The situation of water rights in Chile is of particular interest because it is a wholly privatized system, where rights are traded in the market and therefore water is presented as a commodity. This privatization of water in Chile occurred as part of the process of neo-liberalization since the 1981 Water Code. The results of this study indicate that both concentration and inequality in the distribution of water rights are very high, which undermines a just social development process and facilitates the economic exploitation of the environment. It proposes a profound revision of the application of a mercantile logic to a scarce essential resource for life such as water and explores the importance of its role as a national good for public use.
Keywords: Water.; Gini coefficient.; Concentration.; Privatization; Chile.